STUDI KOMPARASI PEMIKIRAN IMAM AL-GHAZALI DAN BARBARA PRASHNIG TENTANG “LEARNING STYLE” - Wandra Arasdi; Sopiatun Nahwiyah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This research aims to find out Imam Al Ghazali and Barbara Prashnig’s thoughts on learning style. In addition, it is intended to see the similarities and differences of the two figures’ thinking which are equally generate his thoughts about the need of learning style in the learning process. The data were collected by using documentation method. The method was done through by collecting books written by Barbara Prashnig and Imam Al-Ghazali as well as books written by other figures, magazines, and journals that contain descriptions of Imam Al-Ghazali and Barbara Prashnig’s thoughts learning style. According to Suharsimi Arikunto, documentation study is done by looking for data about things or variables in the form of notes, transcripts, books, magazine newspapers, inscriptions, meeting minutes, agenda and so on. Since the type of research is a library research and the data collection method used is documentation method. Therefore, the data analysis was done through content analysis. Content analysis is a technique for studying documents. This is in line with Hilun who stated that the research describes content analysis technique in which the technique was used to analyze and understand the text. This technique seeks to describe objectively, systematically and quantitatively. Based on the research findings, it can be concluded that Imam Al Ghazali defined learning styles as Ta’lim Insani (learning by using the senses and tafakkur), Ta'lim Rabbani (revelation and ilham), comfortable environment, exemplary, and demonstration. Meanwhile, Barbara Prashnig defined it as right/left brain dimension, sensory modalities, physical needs, environment, social and attitude grouping. The similarities of Imam Al Ghazali and Barbara Prashnig's thoughts on learning style are: learning style. The differences are sensory modalities, integrity, environment, attitude/morals and the learners’ needs, heart, revelation, inspiration, obstacle and demonstration.